Analysis of Implementation Barriers and Gaps in the Adoption of Chip-Based (Cashless) E-Money in Non-Cash Payment Systems in Pontianak City - Sri Haryaningsih; Farah Devi Andriani; Rizal Ubaydillah; Hansen Hansen (Journal Of Data Science, 2026)
Digital transformation in payment systems encourages the use of non-cash instruments, including chip-based e-money which has advantages in transaction speed and efficiency. However, its implementation at the regional level still faces various obstacles. This research aims to analyze implementation barriers and gaps in the adoption of chip-based e-money in Pontianak City. The method used is a quantitative approach with an explanatory research design. Data was collected through a questionnaire among people who use chip-based e-money and analyzed using SEM-PLS. The research results show that the factors perceived ease of use, benefits, security, trust, digital financial literacy, as well as infrastructure and policy support influence the adoption of chip-based e-money. Apart from that, it was found that there was a gap between the designed policies and the reality of implementation in the field. This research recommends strengthening digital literacy, improving infrastructure, and optimizing policies to encourage wider use of chip-based e-money.